2020
DOI: 10.1002/eap.2048
|View full text |Cite
|
Sign up to set email alerts
|

Drought exacerbates negative consequences of high‐intensity cattle grazing in a semiarid grassland

Abstract: Grasslands managed for grazing are the largest land‐use category globally, with a significant proportion of these grasslands occurring in semiarid and arid regions. In such dryland systems, the effect of grazing on native plant diversity has been equivocal, some studies suggesting that grazing reduces native plant diversity, others that grazing increases or has little impact on diversity. One impediment toward generalizing grazing effects on diversity in this region is that high levels of interannual variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 153 publications
(212 reference statements)
3
28
1
Order By: Relevance
“…There was a reduction in ANPP associated with grazing during dry years that did not occur in wet years. This finding is in agreement with studies conducted in grasslands of Asia, Europe, and North America (Liang et al, 2018;Stampfli et al, 2018;Souther et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…There was a reduction in ANPP associated with grazing during dry years that did not occur in wet years. This finding is in agreement with studies conducted in grasslands of Asia, Europe, and North America (Liang et al, 2018;Stampfli et al, 2018;Souther et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…This outcome had significant contributions to IHF, particularly in caged plots (Figure 6c). Other studies have documented high establishment of invading annuals following a drought (Puritty et al., 2019; Souther et al., 2020), and it seems likely that reduced biotic resistance in drought and drought relief plots, combined with relatively high soil moisture in spring (Figures ) increased vital rates early in the life cycle in 2014. Thus, part of the observed effect of the drought relief treatment was driven by factors prior to the implementation of drought relief.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, several studies have shown that high grazing pressure in pastures with low grass density reduces seed production and limits the potential of grasses to (re)invade niches (O’Connor and Pickett, 1992; Tessema et al, 2016). In addition, the effects of intensive grazing on the resilience of grasses are assumed to be greater under drought conditions (Souther et al, 2020).…”
Section: Discussionmentioning
confidence: 99%